Evaluasi Tingkat Kepuasan Pengguna Terhadap Aplikasi Sarana Penghubung Ar Rahman dengan Pendekatan PIECES - Ami, Hidayati; Saputra, Ariansyah; Deviana, Hartati (Jurnal Teknologi Terapan and Sains 4.0, 2026)
This research focuses on assessing the level of user contentment (consisting of Parents, Teachers, and Administrators) regarding the utilization of the Ar Rahman Communication Facility Application (SAPA Rahman). This application functions as a critical communication bridge and information hub between the boarding school and the guardians of students. The evaluation methodology adopted the PIECES framework, which measures six core criteria: Performance, Information, Economy, Control, Efficiency, and Service. The sample size was determined using the Slovin formula, resulting in 241 Parent respondents, 8 Administrators (full population), and 67 Teachers. Data analysis concludes that all user groups achieved a remarkably high satisfaction rating. The overall mean satisfaction scores recorded were 4.31 (Very Satisfied) for Parents, 4.28 (Very Satisfied) for Administrators, and 4.27 (Very Satisfied) for Teachers. These findings demonstrate that SAPA Rahman has successfully met the operational expectations of its users. Kata kunci: User Satisfaction, SAPA Rahman Application, System Evaluation, PIECES Model.